Experiencias de los cuidadores de pacientes con enfermedad crónica degenerativa Programa Joaquín Gallegos Lara, MIES Guaranda 2019 - Chariguamán Chimbo, Johana Elizabeth (2019)
Introduction: Chronic diseases are characterized as long-term degenerative diseases where patients gradually lose self-care abilities. It is there where the patient, thanks to humanized care, manages to meet his needs for self-care and cope with the disease with emotional support based on the trust, love and respect of a family member. This work is a study that emerges from the scarce information available to address the experiences of family caregivers, based on the needs expressed by patients and also how has been their adaptation process, their needs and the emotions that accompany them. Purpose: To reveal experiences of the caregiver of a person with chronic degenerative disease, through an in-depth interview in order to strengthen and sensitize humanized care, based on an understanding of the reality of family caregivers. Methodology: The case study It was based on the qualitative typology that the case study uses as a design applying the phenomenological approach. An in-depth interview was previously prepared with a total of 12 questions that were analyzed through a hermeneutical unit in the qualitative Atlas Ti 8.3 software, through which the categorization and codification of the comments was carried out, facilitating their understanding of phenomenological analysis. Results: The information collected through in-depth interviews allowed us to know the reality of caregivers, exalting how, despite experiencing emotions of sadness, depression, caregivers manage to cope with their emotions due to their deep emotional commitment to their family members, in the same order of ideas evidenced the need for information relevant to the care required by patients, in addition to the economic difficulties caused by expenses in treatment and the impediment to keep a job in conjunction with their role as caregiver. Conclusion: Thanks to the study, the emotions experienced by caregivers were revealed, affecting them mentally and physically, as well as the existence of a psychic, physical and economic commitment affecting the normal course of their lives. In another order of ideas, it was observed that caregivers use support in their religious and spiritual beliefs as support, which gives them strength and resignation to the situation their family is going through. As a close after analyzing the experience of the caregiver as a whole, it was noted that it presents problems and support needs, even is at risk of burned career syndrome, therefore, nursing intervention is important since we are leaders in provide care for vulnerable people Keywords: Family caregiver, emotions, support, chronic illness